Clinical, radiological and pathological features of anti-MDA5 antibody-associated interstitial lung disease - Xin Lu; Min Liu; Lu Zhang; Wei Jiang; Guochun Wang; Qinglin Peng; Ruie Feng; Xixia Chen; Qiwen Jin; Sang Lin; Yuli Wang; Aiping Song (RMD Open, 2023)
Introduction To investigate the clinical, radiographic and pathological features of interstitial lung disease (ILD) in patients with anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (anti-MDA5+DM).Methods We retrospectively analysed the medical records of patients with anti-MDA5+DM who had undergone radiological examination, and lung histopathology was performed on 17 of them.Results This study examined 329 patients with anti-MDA5+DM, of whom 308 (93.6%) were diagnosed with ILD and 177 (53.8%) exhibited rapidly progressive ILD (RPILD). The most common radiographic patterns were organising pneumonia (OP) (43.2%), non-specific interstitial pneumonia (NSIP) (26.4%) and NSIP+OP (18.5%). Histological analysis showed NSIP (41.2%) and NSIP+OP (47.1%) to be the predominant patterns. However, in the 17 patients who underwent lung histopathology, the coincidence rate between radiological and histopathological diagnoses was only 11.8%. Compared with patients without RPILD, those with RPILD showed a higher prevalence of NSIP+OP (26.6% vs 10.7%, p=0.001) and a lower prevalence of NSIP pattern (21.5% vs 37.4%, p=0.002) on high-resolution CT. Furthermore, patients with radiographic patterns of NSIP+OP or diffuse alveolar damage (DAD) had more risk factors for poor prognosis, with 12-month mortality rates of 45.9% and 100%, respectively.Conclusions RPILD was commonly observed in patients with anti-MDA5+DM. OP was identified as the predominant radiographic pattern, which corresponded to a histopathological pattern of NSIP or NSIP+OP. Notably, patients exhibiting radiographic patterns of NSIP+OP or DAD were shown to have a poor prognosis.